posted by angela .
convert the compound statements into words p= babies eat bananas q= babies do not sleep through the night ~(P arrow q)
~ means not
p-> q means if p then q
Be aware that:
~(p->q) is equivalent to ~q -> ~p
What you need is:
~(if babies eat bananas, then they sleep through the night)
if babies don't sleep through the night, then they do not eat bananas.
if babies don't sleep through the night, then they didn't eat bananas.
(note: the change in tense is to make it easier to understand)
dodecagon with a perimeter of 108 cm